Currículo do curso de Enfermagem da Universidade Federal de Minas Gerais (EEUFMG): perspectiva de docentes e discentes - Vânia Aparecida da Costa Oliveira (2016)
The institution of the National Curricular Guidelines for Undergraduate Nursing Courses (Diretrizes Curriculares Nacionais/Enfermagem [DCN/ENF]), in November 2001, constitutes a milestone in the reorientation of college education for nursing professionals. These guidelines restate the need for and obligation of educational institutions to train their professionals to meet the healthcare needs of the general population in the broadest sense, with special emphasis on the Brazilian Universal Healthcare System (Sistema Único de Saúde [SUS]), and to ensure the completeness of healthcare delivery, centered on quality care and humanization. In order to adapt to this new reality, in 2009, the UFMG School of Nursing (Escola de Enfermagem da Universidade Federal de Minas Gerais [EEUFMG]) initiated a process to effect a change in its curriculum. In view of this change and the challenges pinpointed in the literature concerning DCN/EF operationalization, this study sought to understand effectuation of the principles of completeness, interdisciplinarity, articulation between theory and practice, and articulation between education and service in the Nursing course curriculum at EEUFMG. This is a single-case study using a qualitative approach whose theoretical framework lies in Bernsteins (1996) concept of recontextualization, classification and framing. The data were collected in semi-structured interviews using a set of open-ended questions and by documentary analysis of EEUFMGs Pedagogical Course Project (Projeto Pedagógico do Curso [PPC]). Ten tenured faculty and fourteen senior year students of the undergraduate nursing course participated in this study. Data were collected from February to May 2015. Data analysis was performed using Norman Faircloughs (2001) Critical Discourse Analysis (CDA) technique. The results revealed that despite EEUFMGs efforts to effectuate the curricular principles scrutinized in this study, many challenges remain. It was observed that there was lack of interdisciplinary integration, fragmentation between basic cycle and professional cycle; weaknesses in the proposition of interdisciplinarity as a strategy to break down established boundaries across disciplines, knowledge and subjects; maintenance of traditional educational order in which theory precedes practice, reaffirming the thinking that knowledge precedes doing and understanding, and that knowledge is constructed progressively and linearly. There is still a gap between nursing education and health services, revealing the absence of effective partnership between these institutions in terms of sharing responsibility for the nursing professionals training. On examining the findings in the light of Bernstein's Theory, it could be seen that the curriculum, as an official document of EEUFMG policy, is undergoing recontextualization processes which are modifying the original proposal. Classification and framing of the institutions curriculum were both found to be strong; thus, exhibiting proximity to the collection code type curriculum. On the other hand, integrality of subject and integrality of care are seen to be effective, and the Rural Nurse Internship program constitutes a space/time learning experience conducive to the effectuation of curricular principles. One can therefore conclude that it is necessary to increase investment in curricular framework so that these principles can be effected throughout the educational process.